TINJAUAN YURIDIS BATAS KEWENANGAN ANTARA TENTARA NASIONAL INDONESIA DAN POLISI REPUBLIK INDONESIA DALAM MENINDAK TINDAK PIDANA TERORISME - Bella Shintia Anggraini; Erdianto Effendi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Terrorism act in various form, keep growing and expand to numerous country after the occupancy of global coalision. According to Romli Atmasasmita, in its progress it can cause jurisdiction conflict to the nations relationship among the countries who has interest in solving dangerous criminal cases that crosses territories. Criminal terrorism act is no longer just a national safety issues, also embrace defence and soveregnty of a nation, so as it need an extraordinary and multidimentional law enforcement in act and institution involvement in it. That effort can implemented by the involvement of TNI in handling criminal terrorism act. Indipendent and collaborative with POLRI. TNI involvement in handling criminal terrorism act meant as involvement to optimised Police role (Badan Nasional Penanggulangan Terorisme) in solving criminal terrorism prevention act in indonesian, which is by status and function to face obstacle in implementation of its duty and the fungction of preventing the criminal terrorist act.The purpose of writing this thesis, namely: First, to figure out the authority of Indonesian National Army (Tentara Nasional Indonesia) in preventing the criminal terrorism act in indonesian. Second, to figure out the involvement of Indonesian National Army (Tentara Nasional Indonesia) in preventing the terrorist in Indonesian.From the results of the study, based on two problem formulations can be concluded. First, TNI’s authority in preventing Criminal terrorism act in Indonesian law number 34 year 2004, law number 3 year 2002 about national defence article 7 section(2), and law number 5 year 2018 letter I section (3)about President as the highest man in charge in running the nation defence which helped by national defence as president’s advisor in establishing the policy of national defence. To face the terrorism threat , President in charge to assign TNI with DPR approvement. Second, TNI need to involved prevent criminal terrorism act in Indonesian because TNI has capability in inteligence, teritorial, combat and safety. TNI intelligence network can support and inform crutial information and detect terrorism network and activity in indonesian to TNI anti terrorisst force or other law enforcement. That capability need to use and become important matter in strategic national terrorism prevention.Keywords: Judicial Review - TNI – Terrorism.